Case report and brief literature review: possible association of secukinumab with Guillain–Barré syndrome in psoriasis - Liang, Gang; Han, Yongmei; He, Haiyan; Lu, Ci; Zhu, Chen (Frontiers in Immunology, 2024)
The etiology of Guillain-Barré syndrome (GBS) may be autoimmune. About two-thirds of patients typically experience their first symptoms within 5 days to 3 weeks after common infectious diseases, surgery, or vaccination. Infection is a triggering factor for over 50% of patients. In recent years, a growing number of studies have indicated that some immune checkpoint inhibitors and COVID-19 may also contribute to the occurrence of GBS. However, drugs are considered a rare cause of GBS. The patient in our case was a 70-year-old male who developed GBS after initiating secukinumab for psoriasis. Upon diagnosis suggesting a potential association between secukinumab and the development of GBS, as per the Naranjo Adverse Drug Reaction (ADR) Probability Scale, we decided to discontinue the drug. Following this intervention, along with the administration of immunoglobulin, the patient exhibited a significant improvement in extremity weakness. The association of GBS with secukinumab treatment, as observed in this case, appears to be uncommon. The underlying mechanisms that may link secukinumab to the development of GBS are not yet fully understood and warrant further scientific inquiry and rigorous investigation. However, we hope that this report can raise greater awareness and vigilance among medical professionals to enhance the safety of patients' medication.